Combined Approach of Vasodilators and Surgical Reconstruction in Diabetic Foot Ulcer: Experience in a Tertiary Care Hospital - Ibrahim, Farzana B; Islam, Mohammed Rashedul; Akand, Md Morshed Uddin; Anwar, Raihan; Islam, Md Anwarul; Deb, Anjan Kumar (BIRDEM Medical Journal, 2018)
Background: Diabetic patients frequently suffer from chronic non-healing ulcer on the sole of foot as a result of combined peripheral neuropathy and arterial insufficiency. Many of them end up in amputation. The aim of this study was to see the outcome of diabetic patients presenting with ulcers that showed no signs of healing in sole of the foot for 3 months or more treated with combination of peripheral vasodilators and surgical reconstruction. Methods: A cross sectional study of 249 patients who presented to Plastic surgery department in BIRDEM fromJanuary 2013 toDecember2015 was done. The patients who had existing associated chronic medical illness like Chronic Kidney Disease (CKD) requiring dialysis, malignancy, Status Asthmaticus and foot ulcer withWagner grade 4 and 5 and patients receiving drugs that cause immunosuppression like chemotherapeutic agents, steroids, and methotrexates were excluded from the study. Results: All patients presented with non-healing ulcerations average size of which was 1.48 cm (range, 0.68 to 4 cm) of more than 3 months in various parts of sole of the foot complicated by peripheral neuropathy and/or arterial insufficiency. After the use of peripheral vasodilators, these patients underwent a variety of surgical reconstructions such as simple skin graft, local flaps, regional flaps and distant flaps. In follow up of 3 to 36 months, 194 patients (77.91%) achieved good results, 55(22.08%) patients’ required secondary procedure such as flap revision, debridement or Split thickness skin graft (STSG) due to post operative complications. Conclusion: We conclude that chronic non-healing ulcers in diabetic patients can be successfully treated by combined approach of surgical reconstruction and peripheral vasodilators. Birdem Med J 2018; 8(2): 108-113